Deteksi Formaldehida Menggunakan Glassy Carbon Electrode (GCE) Modifikasi Lapisan Tipis Emas secara Voltametri Siklik - Maharani, Indah Kemala; Sari, Trisna Kumala; Dewata, Indang; Warda Ningsih, Sherly Kasuma; Yamesa Away, Romy Dwipa (Departemen Kimia FMIPA UNP, 2024)
The formaldehyde was found as one of the toxic and mutagenic products. Long-term exposure will harm the health of the human body. This study aims to detect formaldehyde developed on an electrochemical sensor using Glassy Carbon Electrode (GCE) modified with a thin layer of gold as the working electrode by cyclic voltammetry. Electrode modification was carried out by electrodeposition of Au potential-sweeping on electrodes known as Au/GCE electrodes. The resulting electrode has high conductivity and excellent catalytic activity because it is able to provide a large peak current response. In this study, the optimum conditions will be determined based on variations in the electrodeposition cycles of gold thin films and variations in the supporting electrolyte. The optimum cycle of gold thin film electrodeposition was obtained, namely one cycle and 0.1 M KOH as the optimum supporting electrolyte. The peak current obtained is sharper, the sensitivity and stability are also better due to the electrocatalytic properties produced by the high gold thin layer.